Study of early-stage precipitation in Al-Mg-Si(-Cu) alloys by 3D atom probe - Zandbergen, MW (2008)
Hardness measurements and Three-Dimensional Atom Probe (3DAP) were used to characterize the early stages of precipitation in three different Al-Mg-Si alloys (Al-0.50 wt%Mg-1.00 wt%Si) with different Cu contents (0.03 wt%, 0.15 wt%, or 0.80 wt% Cu). Heat treatments were chosen to simulate an industrial production line for car body-sheet material and included natural ageing (NA), pre-ageing at 80 °C (PA), paint-bake ageing at 180 °C (PB) and 10 second ageing at 180 °C (spike). The Cu content and the chosen heat treatments were found to influence the microstructural evolution of the alloy considerably. Based on the determined microstructures and matrix solute concentrations, mechanisms for the effect of NA, PA and Cu additions were proposed. NA had a deleterious effect on the PB hardening response, which was delayed dramatically after 20 minutes NA or longer. When the NA time was 1 minute, β" precipitates were formed within 30 minutes PB resulting in high hardness of the alloy. The delay with NA time was caused by a decrease in the nucleation rate of elongated precipitates during the subsequent PB. This decrease was thought to be due to a combination of a decrease in the matrix solute concentrations and clusters acting as vacancy sinks. PA before NA improved the PB response due to the formation of a high density of short elongated precipitates. Small Mg-Si clusters were detected after both NA and PA. Clusters formed during PA were found to be, on average, Mg-richer and larger than those formed during NA. Larger clusters were found to be more stable during PB and, upon PB, to grow into nucleation sites for elongated precipitates. Application of a spike before PA resulted in faster growth of clusters during PA. Growth of clusters and nucleation of short elongated precipitates during PB was found to be enhanced with increasing Cu content when no PA was given. Cu was found to be present in all precipitates and clusters in the alloy with the highest Cu content. These precipitates were thought to be precursors to the Q' phase.